Analisis Efektivitas, Efesiensi Penerimaan Pajak Hiburan dan Pengaruhnya Terhadap Pendapatan Asli Daerah di Kabupaten Badung - Rame, Christhian; Nata Wirawan, I Gusti Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 10, Oktober 2013 (pp. 434-491), 2013)
Application of Law Number 32 Year 2004 about area autonomy. Policy of area autonomy placing town and sub-province as autonomous emphasis likely promise better expectation to area to be able to develop center diri.Pemerintah give broader kewenangan to local government in managing its area as according to condition of society aspiration and region. Autonomous also give expectation to society to be able to enjoy service of better public, climate creation democratize in area, and also peep out new expectation to society to be able to obtain;get policys of more making account of area of society chance. In this research of research obyek is acceptance of entertainment amusement Iease in Sub-Province of Badung Year 2001-2010. Data the used is data of sekunder obtained of institutions which related to entertainment amusement Iease. Analysis technique the used is efekrivitas, Simple Linear Regression and efesiensi. Pursuant to result of solution can be concluded that (1) effectiveness acceptance of entertainment amusement Iease in Sub-Province of Badung year 2001-2010 mean equal to 121,84 %. (2) efesiensi acceptance of entertainment amusement Iease in Sub-Province of Badung year 2001-2010 mean equal to 5,88%.  3) Acceptance of Iease Entertainment amusement have influence which are positive and signifikan to PAD in Sub-Province of Badung Year 2001-2010.
Keywords: Acceptance of Iease Entertainment amusement; Earnings of Genuiness Area